Design and analysis of key shaped wearable textile antenna - Bano, Nausheen; Kumar Singh, Vinod; Kumar Bhoi, Akash; Sharma, Sanjeev (International Journal of Engineering and Technology, 2018)
The proposed antenna is designed to achieve high gain and wide band with partial ground. In this paper, textile wearable antennas work-ing in the craved range of frequency are fabricated and demonstrated. Simulated and measured reflection coefficient, directivity and radi-ation characteristics have been studied. CST is used for design & simulation of existing antenna with design frequency 3GHz.Â Â